Inhibition of Glycolysis Impairs Retinoic Acid-Inducible Gene I–Mediated Antiviral Responses in Primary Human Dendritic Cells - Zevini, Alessandra; Palermo, Enrico; Di Carlo, Daniele; Alexandridi, Magdalini; Rinaldo, Serena; Paone, Alessio; Cutruzzola, Francesca; Etna, Marilena P.; Coccia, Eliana M.; Olagnier, David; Hiscott, John (Frontiers in Cellular and Infection Microbiology, 2022)
Dendritic cells (DC) are important mediators of the induction and regulation of adaptive immune responses following microbial infection and inflammation. Sensing environmental danger signals including viruses, microbial products or inflammatory stimuli by DC leads to the rapid transition from a resting state to an activated mature state. DC maturation involves enhanced capturing and processing of antigens for presentation by major histocompatibility complex (MHC) class I and class II, upregulation of chemokines and their receptors, cytokines and costimulatory molecules, and migration to lymphoid tissues where they prime naive T cells. Orchestrating a cellular response to environmental threats requires a high bioenergetic cost that accompanies the metabolic reprogramming of DC during activation. We previously demonstrated that DC undergo a striking functional transition after stimulation of the RIG-I pathway with a synthetic 5’ tri-phosphate containing RNA (termed M8), consisting of the upregulation of interferon-stimulated antiviral genes, increased DC phagocytosis, activation of a proinflammatory phenotype and induction of markers associated with immunogenic cell death. In the present study, we set out to determine the metabolic changes associated with RIG-I stimulation by M8. The rate of glycolysis in primary human DC was increased in response to RIG-I activation and glycolytic reprogramming was an essential requirement for DC activation. Pharmacological inhibition of glycolysis in MoDC impaired type I interferon signalling by disrupting the TBK1-IRF3-STAT1 axis, thereby countering the antiviral activity induced by M8. Functionally, the impaired IFN response resulted in enhanced viral replication of dengue, coronavirus 229E and coxsackie B5.